Late outcome of bleeding gastric ulcers. Issue 8 (August 1986) - Smart, H L; Langman, M J
Abstract : The subsequent progress of 152 patients treated medically in the Nottingham hospitals for bleeding gastric ulceration was analysed four to eight years later by the use of life tables. The overall cumulative rate of ulcer haemorrhage, perforation or related death was found to be 19%. Women had a greater rate than men (women 21%, men 14%) but this difference was not statistically significant. The risk of developing a recurrent complication fell with time in both groups. Women were older than men at the time of their index admission and women who suffered a late complication were significantly older than those remaining well at the end of the follow up period. No similar differences existed for men. The risk of having a late complication from a bleeding gastric ulcer compares favourably with that reported under similar circumstances for duodenal ulceration. Attempts to reduce the late complication rate should concentrate on those patients shown to be at a greater risk - that is, elderly women.